Utilizing Saudi volcanic scoria in lightweight geopolymer for enhanced wellbore cementing - Idham K. Rahmatullah; Abdulmalek Ahmed; Salaheldin Elkatatny; Ahmed M. Abd El Fattah (Scientific Reports)
Abstract Geopolymer cement represents an innovative and environmentally friendly cement system that utilizes non-portlandite precursors to achieve cement hardening. Unlike traditional Portland cement, which accounts for approximately 5–8% of global CO₂ emissions, geopolymer cement offers a sustainable alternative. While its use has been widely adopted in construction projects, its application in wellbore cementing remains limited. Beyond reducing CO₂ emissions, geopolymer cement optimizes waste management by incorporating rock-based or industrial by-products rich in aluminosilicate content. In this study, Saudi volcanic scoria was developed as the primary binder for lightweight geopolymer wellbore cement. By varying the concentration of sodium hydroxide (NaOH) as an alkali activator from 15 to 40%, lightweight geopolymer cement was produced without the addition of external additives. The geopolymer cement sample containing the optimum concentration of NaOH was then used as a benchmark and compared to traditional Portland cement under identical conditions. Key variables such as mechanical strengths, rheological properties, free water, and sedimentation were analyzed. Experimental results demonstrated that volcanic scoria-based geopolymer cement with 20% NaOH achieved optimal performance, with the highest compressive and tensile strengths of 1798 psi and 73.9 psi, respectively. The results revealed that the geopolymer cement outperformed Portland cement in several aspects. For example, its compressive strength was 56% higher than that of Portland cement. Furthermore, the elastic properties of geopolymer cement were superior, with a 47% lower Young’s modulus than Portland cement. Rheological evaluations indicated that geopolymer cement exhibited excellent pumpability and workability. Despite its plastic viscosity being higher than Portland cement, the geopolymer cement demonstrated 180%, 200%, and 336% higher yield points, 10-second gel strengths, and 10-minute gel strengths, respectively. Geopolymer cement performed exceptionally well in terms of stability, with 96% less free water and a 14% lower density variation than Portland cement. These findings highlight the potential of Saudi volcanic scoria as a primary binder in lightweight geopolymer cement. By applying the one-part method, the volcanic scoria-based geopolymer cement becomes a prospective environmentally friendly cement that can potentially be used in wellbore operations. It offers a viable solution that mitigates the carbon emissions while meeting the technical requirements for wellbore cementing applications.